Does Water Enable Porosity in Aluminosilicate Zeolites? Porous Frameworks versus Dense Minerals - Asselman, Karel; Haouas, Mohamed; Houlleberghs, Maarten; Radhakrishnan, Sambhu; Wangermez, Wauter; Kirschhock, Christine E A; Breynaert, Eric (Crystal growth & design, 2023)
Recently identified zeolite precursors consisting of concentrated, hyposolvated homogeneous alkalisilicate liquids, hydrated silicate ionic liquids (HSIL), minimize correlation of synthesis variables and enable one to isolate and examine the impact of complex parameters such as water content on zeolite crystallization. HSIL are highly concentrated, homogeneous liquids containing water as a reactant rather than bulk solvent. This simplifies elucidation of the role of water during zeolite synthesis. Hydrothermal treatment at 170 °C of Al-doped potassium HSIL with chemical composition 0.5SiO :1KOH: H O:0.013Al O yields porous merlinoite (MER) zeolite when H O/KOH exceeds 4 and dense, anhydrous megakalsilite when H O/KOH is lower. Solid phase products and precursor liquids were fully characterized using XRD, SEM, NMR, TGA, and ICP analysis. Phase selectivity is discussed in terms of cation hydration as the mechanism, allowing a spatial cation arrangement enabling the formation of pores. Under water deficient conditions, the entropic penalty of cation hydration in the solid is large and cations need to be entirely coordinated by framework oxygens, leading to dense, anhydrous networks. Hence, the water activity in the synthesis medium and the affinity of a cation to either coordinate to water or to aluminosilicate decides whether a porous, hydrated, or a dense, anhydrous framework is formed.